3x+-2y=11

Simple and best practice solution for 3x+-2y=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+-2y=11 equation:


Simplifying
3x + -2y = 11

Solving
3x + -2y = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2y' to each side of the equation.
3x + -2y + 2y = 11 + 2y

Combine like terms: -2y + 2y = 0
3x + 0 = 11 + 2y
3x = 11 + 2y

Divide each side by '3'.
x = 3.666666667 + 0.6666666667y

Simplifying
x = 3.666666667 + 0.6666666667y

See similar equations:

| 3x-28=5(1-6x) | | 3(y-6)+5y=6 | | 4x+12=1x-6 | | -3(2z-8)-2(z-8)-9z= | | 4b+18=-12b | | -6+3y=2y+4 | | 3k*5=2*3k | | K+32=28 | | -6x-2(x+2)=2(1-5x) | | -33=3(u+3)+3u | | 15-5x+15+2+1=2x-2+10+2 | | 3x^2+1x+6=0 | | -15+n=-0 | | 23y+90+4(10.25-0.125y)+4=180 | | X+15=25+12 | | -3(x+5)-3x=5-(2+x)+7 | | 142=7+3(-7x+3) | | g-1.6=2.8 | | .8*X=24 | | 14+12v=-16+9 | | 20-43=3(x-1)-5 | | 0=6x+13 | | j-3.79=14.21 | | 21y-1=4x+23+9x-38 | | y=6(0)+13 | | 80*X=24 | | x+2x+(x+3)=75 | | 11b-12=-10 | | f+6=8 | | 6(5)-1=5(5-1)-3(7-2(1)) | | 5=q+2 | | 9(0)-7y=14 |

Equations solver categories